2019
DOI: 10.1097/md.0000000000017827
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical overexpression of BCL-2 protein predicts an inferior survival in patients with primary central nervous system diffuse large B-cell lymphoma

Abstract: This study was designed to analyze the clinical characteristics and prognostic value of c-MYC and BCL-2 proteins expression in patients with primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL).82 patients newly diagnosed with PCNS-DLBCL, from January 2008 to November 2018, were enrolled in this study. Clinical characteristics, immunohistochemical features, laboratory examinations, and treatment outcome were analyzed among these patients.Among these 82 cases, 45 were males (54.9%) and 37 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 32 Interestingly, double expression and concurrent BCL6 overexpression is frequently observed in extranodal lymphomas, including primary CNS DLBCL (∼80%) and primary cutaneous DLBCL (leg type) (∼70%). 11 , 12 , 13 , 24 , 33 , 34 , 35 Our analysis revealed a high incidence of double expression in the ABC subtype: 77% (52/68) vs 18% (8/44) in the GCB subtype ( P < .001) and high rates of BCL6 overexpression in both subtypes, 77% in ABC subtype vs 88% in GCB subtype ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 74%
“… 32 Interestingly, double expression and concurrent BCL6 overexpression is frequently observed in extranodal lymphomas, including primary CNS DLBCL (∼80%) and primary cutaneous DLBCL (leg type) (∼70%). 11 , 12 , 13 , 24 , 33 , 34 , 35 Our analysis revealed a high incidence of double expression in the ABC subtype: 77% (52/68) vs 18% (8/44) in the GCB subtype ( P < .001) and high rates of BCL6 overexpression in both subtypes, 77% in ABC subtype vs 88% in GCB subtype ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 74%
“…Four tumors in this group exhibited a small number of chromosomal gains/losses (<5/tumor), while the quantity of chromosomal aberrations was high (5+) in the remaining 4 tumors. No differences in radiologic or histologic features between these pediatric type PCNS-LBCL and their adult type counterparts was appreciable (Figure 2A-F Kaplan-Meier survival analysis demonstrated a 5-year overall survival (OS) of 100% for the pediatric type, MYD88-wildtype group, which was substantially longer than PCNS-LBCL in adult patients from previous studies [15][16][17][18][19][20] (Figure 2G, Sup. Tables 8-9).…”
Section: Clinical Trial Registration Information (If Any)mentioning
confidence: 79%
“…A previous study revealed that Bcl-2, as one of the vital apoptosis suppressor genes, can effectively regulate the development and differentiation of normal B cells ( 40 ). High expression levels of Bcl-2 were reported in ~45% of patients with DLBCL ( 41 ). In addition, patients with DLBCL and high expression levels of Bcl-2 have a significantly worse prognosis with R-CHOP treatment ( 42 ).…”
Section: Discussionmentioning
confidence: 99%